Concerning Specific Features of M&A Management - X. V. Sadykova; E. S. Biryukov (Вестник Российского экономического университета имени Г. В. Плеханова)
Today global and national economy is facing numerous hardly predictable events, which N. Talleb called ‘the black swam’ events, i.e. events having serious consequences both for economy in general and for industries in particular. Integrated corporate structures are still being formed at the expense of M&A deals. Statistic and diagnostic of M&A deals in leading companies testify that these deals have a high degree of risk, while classical management in M&A developed in the last 20 years requires drastic changes. Finance community considers acquisition of new businesses as a conventional method of getting different preferences, such as knowledge and skill diffusion in the field of innovation, opportunity of penetrating new markets, possible obtaining the synergy effect, including one within the frames of ‘the so-called ‘mum’s bias’. By studying global and home experience we can clearly observe that the majority of companies-buyers (or companies-aggressors) pursue policy of acquisition in respect of companiestargets, in other words, the company-target is not considered as an object of any investment. It could be investment in capital, in optimization of the system of strategic management in the company-target or in upgrading businessmodel, etc. In this respect the authors study specific features of corporate management within the frames of ShareholderActivism, non-executive directors and agent theory, identify contradictions and show changes in these fields.